2022
DOI: 10.1101/2022.12.21.521435
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A Spatiotemporal Notch Interaction Map from Membrane to Nucleus

Abstract: Notch signaling relies on ligand-induced proteolysis to liberate a nuclear effector that drives cell fate decisions. The location and timing of individual steps required for proteolysis and movement of Notch from membrane to nucleus, however, remain unclear. Here, we use proximity labeling with quantitative multiplexed mass spectrometry to monitor the microenvironment of endogenous Notch2 after ligand stimulation in the presence of a gamma secretase inhibitor and then as a function of time after inhibitor remo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 76 publications
(100 reference statements)
1
6
0
Order By: Relevance
“…The accumulation of steady-state levels of NICD in the nucleus by ~45 min is also in agreement with the observed timing for transcriptional induction of Notch target genes in Drosophila and cell culture systems (Falo-Sanjuan et al, 2019;Ilagan et al, 2011;Pillidge & Bray, 2019). The timing of these dynamics are also similar to that obtained by following the kinetics of proximity labeling of nuclear proteins associated with the Notch transcriptional response which become labeled within 30-45 min of release from GSI inhibition (Martin et al, 2023).…”
Section: Discussionsupporting
confidence: 84%
See 3 more Smart Citations
“…The accumulation of steady-state levels of NICD in the nucleus by ~45 min is also in agreement with the observed timing for transcriptional induction of Notch target genes in Drosophila and cell culture systems (Falo-Sanjuan et al, 2019;Ilagan et al, 2011;Pillidge & Bray, 2019). The timing of these dynamics are also similar to that obtained by following the kinetics of proximity labeling of nuclear proteins associated with the Notch transcriptional response which become labeled within 30-45 min of release from GSI inhibition (Martin et al, 2023).…”
Section: Discussionsupporting
confidence: 84%
“…JAGGED1-Fc expression and purification. Human JAGGED1-Fc (Martin et al, 2023) was transfected into Expi293F cells (ThermoFisher, A14527) using FectroPro (Polyplus, 101000007). Secreted JAGGED1-Fc was recovered from the culture media on Protein A agarose (Millipore, and eluted with 100 mM glycine, pH 3.0.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Endocytosis of Notch regulates protein recycling [44] and degradation [45]. Importantly, spatiotemporal analysis using pulses of APEX2 biotinylation [46] mapped discreate Notch interactomes during ligand-induced Notch proteolysis, endocytosis, and nuclear translocation. 696 of 1093 interacting proteins identified by Martin et al were also biotinylated in our experiment (202 of which were nuclear, all shown in S2 Table).…”
Section: Discussionmentioning
confidence: 99%